Fruit ripening specific expression of β-D-N-acetylhexosaminidase (β-Hex) gene in tomato is transcriptionally regulated by ethylene response factor SlERF.E4. (October 2022) - Irfan, Mohammad; Kumar, Pankaj; Kumar, Vinay; Datta, Asis
Abstract: N-glycans and N-glycan processing enzymes are key players in regulating the ripening of tomato ( Solanum lycopersicum ) fruits, a model for fleshy fruit ripening. β-D-N-acetylhexosaminidase (β-Hex) is a N-glycan processing enzyme involved in fruit ripening. The suppression of β-Hex results in enhanced fruit shelf life and firmness in both climacteric and non-climacteric fruits. Previously, we have shown that ripening specific expression of β-Hex is regulated by RIPENING INHIBITOR (RIN), ABSCISIC ACID STRESS RIPENING 1 (SlASR1) and ethylene. However, the precise mechanism of ethylene-mediated regulation of β-Hex remains elusive. To gain insights into this, we have performed 5' deletion mapping of tomato β-Hex promoter and a shorter promoter fragment (pD-200, 200 bp upstream to translational start site) is identified, which was found critical for spatio-temporal transcriptional regulation of β-Hex . Further, site specific mutagenesis in RIN and ASR1 binding sites in pD-200 provides key insights into ripening specific promoter activity. Furthermore, induction of GUS activity by ethylene, yeast one hybrid assay and EMSA identify Ethylene Response Factor SlERF.E4 as a positive regulator of β-Hex . Taken together, our study suggest that SlERF.E4 together with RIN and SlASR1 transcriptionally regulates β-Hex and all these three proteins are essential for fruit ripening specific expression of β-Hex in tomato. Highlights: A shorter fragment of tomato β-Hex promoter (pD-200) is sufficient for ripening specific expression. Ethylene induces pD-200 promoter activity and SlERF.E4 binds to pD-200 promoter. RIN, SlASR1 and SlERF.E4 are transcriptional activators of β-Hex and work in a complementary manner. pD-200 promoter can be used for fruit specific gene expression studies and improving fruit quality traits.